Diabetes - Leslie, R. David (Clinician's desk reference, 2013)
Diabetes: Clinician's Desk Reference aims to provide a clear, concise and handy resource for everyday use by practising physicians. The book explains the underlying pathophysiology of the disease, as well as covering in detail all its main forms and complications. Separate chapters consider the range of treatment options, together with summaries of key clinical trials. Coverage also includes epidemiology and classification, as well as diagnosis, screening, limiting risk, and other aspects of disease management and patient care. The book is illustrated throughout by explanatory diagrams, graphs, tables and photos. The book will be useful for physicians, nurses and allied health professionals with an interest in diabetes whether in primary care, in hospitals or in training. Key Features: -Concise up-to-date volume covers all aspects of diabetes: basic science, clinical practice, laboratory analysis -International authorship for a worldwide readership -Illustrated with diagrams, tables and photos